2022
DOI: 10.1001/jamanetworkopen.2021.44391
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Laparoscopically Confirmed Endometriosis and Risk of Early Natural Menopause

Abstract: IMPORTANCEEarly natural menopause (ENM) has been associated with reduced reproductive span, cardiovascular disease risk, and early mortality. The potential adverse implications of endometrioma surgery for ovarian reserve are known, yet the association of endometriosis with menopausal timing remains understudied. OBJECTIVE To investigate the association between endometriosis and risk for ENM. DESIGN, SETTING, AND PARTICIPANTS This large, population-based cohort study analyzed data from the Nurses' Health Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Clinical findings confirm this trend; one recent, large, prospective cohort study including 106,633 premenopausal, laparoscopically confirmed endometriosis patients found higher risk for early natural menopause compared to those without endometriosis, especially in nulliparous women and in those who never used oral contraceptives ( 139 ). In two recent meta-analysis both serum AMH and AFC were found to be reduced in patients with unoperated endometriomas compared to patients with other benign ovarian cysts without endometriosis ( 140 , 141 ).…”
Section: Pathophysiology Of Endometriosis Associated Infertilitymentioning
confidence: 74%
“…Clinical findings confirm this trend; one recent, large, prospective cohort study including 106,633 premenopausal, laparoscopically confirmed endometriosis patients found higher risk for early natural menopause compared to those without endometriosis, especially in nulliparous women and in those who never used oral contraceptives ( 139 ). In two recent meta-analysis both serum AMH and AFC were found to be reduced in patients with unoperated endometriomas compared to patients with other benign ovarian cysts without endometriosis ( 140 , 141 ).…”
Section: Pathophysiology Of Endometriosis Associated Infertilitymentioning
confidence: 74%
“… 12 , 48 , 49 The quantification of cumulative risk is further complicated by the increased odds of developing a subsequent SS-RF when one already exists for an individual. For example, endometriosis has been linked to greater odds of having an APO, 50 , 51 , 52 , 53 PCOS, 54 early menopause 39 , 55 associated with early age of menarche, 56 , 57 and breast cancer. 58 , 59 Challenges aside, effective screening involves early identification of risk factors that can be addressed with recommended prevention and or treatment guidelines, with the ultimate goal of improving health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Well-designed epidemiological studies of the relationship between age of menopause and endometriosis are lacking [ 39 ]. One study reported an increased risk of early natural menopause (< 45 years) in endometriosis patients [ 40 ]. Potential mechanisms include effects of endometrioma (endometriosis on the ovary) on ovarian function, effects of surgical excision of endometrioma [ 41 ] and effects of endometriosis-related traits such as reduced body mass index [ 39 ].…”
Section: Discussionmentioning
confidence: 99%